The Correlation Between Students’ Speaking Self-Efficacy and Collocation Competence in Speaking at SMPN 1 Parengan - Dinda Vica Ocarina; Khoirul Anwar; Ulfah Marifah (Universitas Muhammadiyah Gresik, 2022)
Speaking, among the four basic language skills – speaking, listening, writing, reading-, is of an exclusive importance in daily life and it is a vital complementary tool in communication skills. Unfortunately, it is not that easy to master English speaking skill and use it to communicate, especially for students who learn English as foreign language (EFL), where they rarely find the situation to use English. Meanwhile, self-efficacy is one of the factors that affect the success of EFL students speaking skill. On the other hand, collocation is a succession of two or more words that must be learned as an integral whole and not pieced together from its component parts which is also an important factor in mastering speaking. This research was carried out to know whether there is a correlation between students’ speaking self-efficacy and collocation competence in speaking. The researcher chose ninth grade students of SMPN 1 PARENGAN to conduct this study. The researcher used the students 9A, 9B, and 9C as the sample which involved 103 students. The data was obtained from a speaking self-efficacy questionnaire and a speaking test. The result of the data correlation coefficient is 0,760 with 0.00 Significant (ρ = 0.00). So, null hypothesis (Ho) can be rejected. It means there is a positive and high correlation between students’ speaking self-efficacy and collocation competence in speaking. It can be concluded that the higher the speaking self-efficacy, the higher the collocation competence in speaking.